2020
DOI: 10.7592/ejhr2020.8.4.waters
|View full text |Cite
|
Sign up to set email alerts
|

The lexical semantics of blaguer: French ways of bringing people together through persuasion, deception and laughter

Abstract: This study presents a lexical semantic analysis of the French verb blaguer and related expressions. This verb belongs to a suite of “French humour practices”, and French-English dictionaries translate it as ‘to joke’. However, Anglo-specific terminology such as “joke” does not match the conceptual semantics of blaguer and its related noun blague. Relying on Anglo-specific terms to categorise culture-specific practices perpetuates conceptual and terminological Anglocentrism. This study furthers the call to avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In addition, to understand a particular culture, semantics is vital in seeing meaning through the community's symbols when performing cultural rituals (Higgins, 2019). Azharbekova et al (2020) and Waters (2020) define cultural semantics as the meaning that a language has according to the culture of its speakers. Sanatifar, S. & Ayob (2022) also suggested that a language's lexicon reflects its cultural environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, to understand a particular culture, semantics is vital in seeing meaning through the community's symbols when performing cultural rituals (Higgins, 2019). Azharbekova et al (2020) and Waters (2020) define cultural semantics as the meaning that a language has according to the culture of its speakers. Sanatifar, S. & Ayob (2022) also suggested that a language's lexicon reflects its cultural environment.…”
Section: Literature Reviewmentioning
confidence: 99%